Voltage and load profiles estimation of distribution network using independent component analysis / Mashitah Mohd Hussain - Mohd Hussain, Mashitah (2014)
This thesis presents research on voltage and load profiles estimation using independent component analysis technique. The uniqueness of this technique is limited information parameters on distribution system required. Usually voltage and load profiles are used as reference to electricity provider when supplying electricity to consumer on proper tariff. Thus, it is important to capture profiles accurately in order to avoid energy wastage and high cost for equipment installation. The work presented in this thesis is using statistical technique to predict voltage profile at source distribution system and load profiles on distribution system. Initially, the research focuses on three main tasks. First, voltage profile on source distribution system is estimated. The voltage profile is predicted using Independent Component Analysis (lCA) algorithm. The voltage profiles are estimated for 24- hours with time interval of 1 minute. Theoretically, when voltage source is controlled, the losses occur on the system is reduced. The task and analysis presented will help system loss their power while transmitting power from transmission to distribution system. Secondly, load profile in a multiple power flow solutions for every minute in 24 hours per day is estimated. A method to calculate multiple solutions of non linear profile is introduced. The Power System SimulationlEngineering (PSS@E) and python has been used to solve the load power flow. The result of this power flow solutions has been used to estimate the load profiles for each load buses using Independent Component Analysis (lCA) without any knowledge of parameter and network topology of the systems. The proposed algorithm is tested with IEEE 69 test bus system which represents the distribution part and the method of ICA has been programmed in MATLAB R2012b version. Next, an electrical load profiles is estimated using limited information to ensure proper power usage measurement of the customers. ICA technique is able to separate the mixed signal into their source signals. Using this method, the load profiles on feeder distribution can be estimated without any knowledge of the network topology and electrical parameters. In addition, a real-time load profiles on feeder distribution can be established instead of load modelling technique by using incoming distribution feeder data profiles. The ability of ICA algorithm to separate the profiles was evaluated. The work is focused on analysing the results of simulation using ICA method including voltage source control and electric losses of the system. Simulation results were obtained in Chapter 4.This thesis compares the result between original and estimated load profiles. Meanwhile, the result of voltage profile is tested on distribution system to investigate losses behaviour. The losses of simulation results with different tap changer and voltage set presented in first task are compared and discussed in this thesis. The estimation quality is verified by using error measures of the load profiles. All simulation results and errors of estimations are discussed in this thesis.